Counterion-mediated enantioconvergent synthesis of axially chiral medium rings - Du, J-Y; Balan, T; Claridge, TDW; Smith, MD (American Chemical Society, 2022)
There are few enantioconvergent reactions in which racemic substrates bearing multiple stereochemical features are converted into products with high levels of diastereo- and enantiocontrol. Here, we disclose a process for the highly enantio- and diastereoselective syntheses of medium ring lactams via an intramolecular counterion-directed C-alkylation reaction. The treatment of racemic biaryl anilides that exist as a complex mixture of enantiomers and diastereoisomeric conformers by virtue of multiple axes of restricted rotation with a quinidine-derived ammonium salt under basic conditions affords medium ring lactams bearing elements of both axial and point chirality via an enolate-driven configurational relaxation process. Thermal equilibration of the syn- and anti-product diasteroisomers has demonstrated that the barriers to bowl inversion are >124 kJ mol-1. We propose that the chiral ammonium salt differentiates between a complex and rapidly equilibrating mixture of enolate and rotational isomers, ultimately leading to highly enantioselective alkylative ring closure. This dynamic and enantioconvergent process offers an operationally simple approach to the synthesis of valuable chiral medium ring lactams for which there are few catalytic and enantioselective approaches.